Resistance is fertile : Canadian struggles on the biocommons - Peekhaus, Wilhelm C. (UBC Press, 2013)
"For decades, government, industry, and the mainstream media have extolled the virtues of biotechnology. Their dominant message -- that biotechnology can improve everything from our health and diet to our environment and economy -- is unmistakably celebratory. We hear about biotechnology's power to reverse environmental degradation, help medical researchers identify disease genes, and increase industrial efficiency, output, and jobs. Government and industry rarely tell us about biotechnology's negative side effects. Not only are genetically engineered crops still failing to deliver consistently higher yields; there is also mounting evidence that genetically engineered organisms come with a host of safety and environmental risks. Focusing on agriculture, Resistance Is Fertile challenges the dominant rhetoric surrounding biotechnology by offering a critical analysis of the role of capital and the state in the development of this technoscience. In particular, Wilhelm Peekhaus analyzes the major issues around which opponents of agricultural biotechnology in Canada are mobilizing -- namely, the enclosure of the biological commons and the knowledge commons, which together form the BioCommons. What emerges is an empirically and theoretically informed analysis of topics such as Canada's regulatory regime, the corporate control of seeds, the intellectual property system, and attempts to construct and control public discussions about agricultural biotechnology."--Publisher's description